2002
DOI: 10.1182/blood.v99.3.754
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic activity of humanized anti-CD20 monoclonal antibody and polymorphism in IgG Fc receptor FcγRIIIa gene

Abstract: Given that the Fc␥RIIIa receptor 158V allotype displays a higher affinity for human immunoglobulin G1 and increased antibody-dependent cellular cytotoxicity, the aim of this study was to determine the influence of that FCGR3A polymorphism on the therapeutic response to rituximab, an anti-CD20 humanized immunoglobulin G1 increasingly used in the treatment of non-Hodgkin lymphomas. The FCGR3A-158V/F genotype was determined in 49 patients having received rituximab for a previously untreated follicular nonHodgkin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

46
1,231
9
15

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,759 publications
(1,322 citation statements)
references
References 37 publications
46
1,231
9
15
Order By: Relevance
“…Efficacy of the treatment in the relapsing follicular lymphoma patients was expected to result from the enhancement of ADCC by rituximab/ BrHPP/IL-2 co-administration. Indeed, polymorphisms in the IgG Fc receptor FccRIIIa gene strongly affect the efficacy of ADCC in patients undergoing rituximab-based therapies 63 and the individual pharmacokinetics for each patient. 64 Therefore, genotyping patients and determining their cancer biomarkers prior to the use of cd cell-based protocols could provide patients with the most appropriate options.…”
Section: Safety Of CD T-cell Activation In Patientsmentioning
confidence: 99%
“…Efficacy of the treatment in the relapsing follicular lymphoma patients was expected to result from the enhancement of ADCC by rituximab/ BrHPP/IL-2 co-administration. Indeed, polymorphisms in the IgG Fc receptor FccRIIIa gene strongly affect the efficacy of ADCC in patients undergoing rituximab-based therapies 63 and the individual pharmacokinetics for each patient. 64 Therefore, genotyping patients and determining their cancer biomarkers prior to the use of cd cell-based protocols could provide patients with the most appropriate options.…”
Section: Safety Of CD T-cell Activation In Patientsmentioning
confidence: 99%
“…Among these mechanisms, studies on rituximab and trastuzumab have suggested that ADCC is the key mechanism of action to eliminate cancer cells. 5-7 …”
Section: Introductionmentioning
confidence: 99%
“…Multiple efforts are made to increase the efficacy of antitumor antibodies, and many strategies focus on modifications serving to increase ADCC of NK cells [5]. Evidence for the importance of the latter has been derived from animal models and analyses with lymphoma patients treated with Rituximab who displayed FcgR polymorphisms (e.g., [6][7][8]). …”
Section: Introductionmentioning
confidence: 99%